PERBANDINGAN KUALITAS DEMOKRASI DALAM PERSPEKTIF KESETARAAN GENDER ANTARA INDONESIA DAN THAILAND - Arin Fithriana; Jeanie Annissa (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2017)
This study discusses the comparative quality of democracy in the perspective of gender equality between Indonesia and Thailand. Selection of study subjects based on data ranking global democracy that puts Indonesia and Thailand as a country in Southeast Asia with the quality of democracy is not far adrift. This study uses the theory of political culture for respective internal uniqueness, the quality of democracy, gender theory and comparative politics approach using Mill's Method to analyze focus of research. This study used a qualitative approach with descriptive type of analysis through literature study. The unit of analysis in this study focused on the quality of democracy in the perspective of gender equality. The unit of explanation is the comparison the quality of democracy in the perspective of gender equality Indonesia and Thailand are seen from the level of political participation of women in each country. Eachby the period between 2010 to 2014 based on internal changes that occur in both. In addition to historical comparative method is also used to acquire the common traits between the uniqueness of the community and assess long-term social change. Based on the data that has been collected relating to the history and political culture of each country, it can be said that the quality of the implementation of democracy is influenced by the historical background and internal changes. Internal change is increasingly open does not necessarily encourage democratization, it is because of the culture of political force. Eventually important role in the political system as a determinant of the quality of democracy and guarantor of democracy.